THE CORPUS OF TRADEMARK NEOLOGISMS IN UZBEK LANGUAGE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article explores the emergence of trademark neologisms in the Uzbek language, focusing on how commercial terms, especially brand names, contribute to the language’s evolution. The study highlights both foreign-derived and native Uzbek neologisms, emphasizing their sociolinguistic impact in the context of globalization. The creation of a corpus of these neologisms is proposed to systematically document their origins, adaptations, and usage. The article examines the balance between linguistic borrowing and the preservation of Uzbek language identity, offering insights into the future trajectory of the language as it integrates new commercial terms.